Making Maoshan Great Again: Religious Rhetoric and Popular Mobilisation from Late Qing to Republican China (1864–1937) - Qijun Zheng (Religions)
This study investigates how religious rhetoric and popular mobilisation contributed to the preservation and propagation of Daoist traditions at the mountain Maoshan 茅山 from late Qing to Republican China (1864–1937), focusing particularly on the corpus of religious texts related to Maoshan and its tutelary gods, the Three Mao Lords 三茅真君. Through a detailed analysis of primary sources, including editions of the Maoshan Gazetteer, liturgical manuals such as the scripture (jing 經), litany (chan 懺), and performative texts such as the precious scroll (baojuan 寶卷) of the Three Mao Lords, this study identifies six key rhetoric strategies employed by Maoshan Daoists, using the acronym IMPACT: (1) Incorporation: Appending miracle tales (lingyan ji 靈驗記) and divine medicine (xianfang 仙方) to address immediate and practical needs of contemporary society; (2) Memory: Preserving doctrinal continuity while invoking cultural nostalgia to reinforce connections to traditional values and heritage; (3) Performance: Collaborating with professional storytellers to disseminate vernacularized texts through oral performances, thereby reaching broader audiences including the illiterate. (4) Abridgment: Condensing lengthy texts into concise and accessible formats; (5) Canonization: Elevating the divine status of deities through spirit-writing, thereby enhancing their religious authority; (6) Translation: Rendering classical texts into vernacular language for broader accessibility. Building upon J.L. Austin’s speech act theory, this study reconceptualizes these textual innovations as a form of “text acts”, arguing that Maoshan texts did not merely transmit religious doctrine but actively shaped pilgrimages and devotional practices through their illocutionary and perlocutionary force. Additionally, this study also highlights the crucial role of social networks, particularly the efforts of key individuals such as Zhang Hefeng 張鶴峰 (fl. 1860–1864), Long Zehou 龍澤厚 (1860–1945), Jiang Daomin 江導岷 (1867–1939), Wang Yiting 王一亭 (1867–1938) and Teng Ruizhi 滕瑞芝 (fl. 1920–1947) who facilitated the reconstruction, reprinting and dissemination of these texts. Furthermore, this study considers pilgrimages to Maoshan as a form of popular mobilisation and resistance to anti-clerical and anti-superstition campaigns, illustrating how, against all odds, Maoshan emerged as a site where religious devotion and economic activity coalesced to sustain the local communities. Ultimately, despite the challenges identified in applying speech act theory to textual practices, the findings conclude that the survival and revival of Daoist traditions at Maoshan was not only a result of textual retention and innovation but also a testament to how religious rhetoric, when coupled with strategic social engagement, can fuel popular mobilisation, reignite collective devotion, and reshape cultural landscapes in transformative ways.